Evaluasi penggunaan profilaksis antibiotik bedah umum di Rumah Sakit Pemerintah di Yogyakarta - Happy Elda Murdiana (Health Sciences and Pharmacy Journal, 2022)
Surgical Site Infections (SSI) is an infection with surgery and surgical procedure, which occurs in the incision area or around the tissue. SSI increases the incidence of patients being admitted to the Intensive Care Units (ICU) by 60%, 5 times being hospitalized and 2 times dying. Giving prophylactic antibiotics before and after surgery will help reduce SSI if the administration of the appropriate type of drug, appropriate dose, appropriate time, and route of administration. The purpose of the study is to analyze the accuracy of the selection to reduce the incidence of SSI. This study is a cross-sectional study with retrospective data collection through the medical records of patients with general surgery in March 2019 with data from January until February 2019. The data collection technique was in the form of total sampling with inclusion and exclusion criteria. Data analysis was carried out by evaluating the use of prophylactic antibiotics and accompanying drugs descriptively and analytically in percentage. The result of the study using prophylactic antibiotics in 51 general surgery patients received the result that preoperative antibiotics were given in 98% of patients, all of the patients received antibiotics with the appropriate indication, an appropriate type of drug, and appropriate route of administration but 78,42% of patients received underdose for cefuroxime and ceftriaxone.  Postoperative antibiotics were given to 80,39% of patients and all patients received appropriate indication and route of drug administration, but 15,68% of patients received an inappropriate type of antibiotic, namely ceftriaxone, and 52.93% of patients received an inappropriate dose, namely cefuroxime (underdose), cefazolin (underdose) and metronidazole (overdose). The results of this study can be used as a consideration for the selection of appropriate prophylactic antibiotics to prevent the occurrence of SSI. Keywords: prophylactic antibiotic, general surgery, cephalosporin